Magnetohydrodynamic boundary layer flow and heat transfer on a continuous moving wavy surface - Hossain, M.A.; Pop, I. (Archives of Mechanics, 1996)
The problem of the boundary layer flow and heat transfer on a continuous moving wavy surface in a quiescent electrically conducting fluid with a constant transverse magnetic field is formulated. The resulting parabolic differential equations are solved numerically using the Keller-box scheme. Detailed results for the velocity and temperature fields are presented, and also the results for the skin-friction coefficient and the local Nusselt number. These results are given for different values of the amplitude of the wavy surface and magnetic parameter when the Prandtl number equals 0.7. It is shown that the flow and heat transfer characteristics are substantially altered by both the magnetic parameter and the amplitude of the wavy surface.